Particle Vertical Mixing and Horizontal Conveyance Within an Ambient Temperature Fluidized Bed - Jawad Khalaf; Braden Smith; Haden Harper; Nathan Schroeder (SolarPACES Conference Proceedings)
Previous studies have shown the advantages of particle-to-sCO2 fluidized bed (FB) heat exchangers, which include high heat transfer coefficients, low material cost, and the ability to horizontally convey solid particles. This paper outlines the design and testing of a compact cold flow FB test apparatus to characterize horizontal conveyance through convolutions within a 100 kWth FB heat exchanger design. Horizontal conveyance is an advantage in FBs because it enables more compact designs for heat exchangers. Two mass flow rates, 0.5 & 1 kg/s, at the inlet & outlet of the FB. To determine consistency of the flow rates, Student’s t-tests were used to assess whether the inlet & outlet values were statistically similar. The mass flow rate exiting the bed was statistically similar to the flow rate entering the bed for both cases, but each case featured a wider range and standard deviation. The range and standard deviation of the 1 kg/s flow rate was 0.69-1.23 kg/s and 0.12 kg/s respectively, and the 0.5 kg/s test featured a range and standard deviation of 0.37-0.73 kg/s and 0.09 kg/s, respectively. These measurements provide confidence that large-scale designs can successfully horizontally convey particles at ````~1.5x minimum fluidization velocity (Umf) without significant variation in flow rate. A method to characterize the degree of particle vertical mixing and bubble frequency within the FB is also introduced. By using a high-resolution camera together with particle velocimetry, particle motion in the X and Y directions can be estimated to assess bed mixing and bubble frequency.